Unexpected species diversity in the understanding of selenium-containing soil invertebrates - Bin Mao; XiangLiang Fang; HongLing Lei; YunLi Xiao; Yue Fu (Scientific Reports)
Abstract Yutangba, situated in Enshi City, Hubei Province, is globally noted for its high selenium (Se) content. Soil invertebrates are essential to the functionality and services of terrestrial ecosystems, yet their community composition in this region remains under-explored. This study utilized environmental DNA metabarcoding to investigate the interrelations among environmental factors, soil invertebrate diversity, and community characteristics concerning soil Se content, pH, and moisture content in the region. Environmental factors such as Se concentration, water content, and pH were strongly associated with species beta diversity of soil invertebrates in Se-rich areas, reshaping their distribution and abundance, while alpha diversity remained relatively stable. Among these, Se notably emerges as the primary regulatory factor increasing soil invertebrate diversity. The acidic soil pH, along with moisture, plays a fine-tuning role in regulating the species richness and community composition. Unexpectedly, certain species, such as the Formicidae (ants, e.g., Odontomachus troglodytes), the Noctuidae (e.g., Diarsia rosaria), and the annelid Haplotaxida Perionyx excavates, exhibit a strong positive association with Se, indicating a high level of Se tolerance among the native species. This novel perspective reveals the complex role of Se in soil ecosystems, emphasizing the necessity of understanding its ecological functions and potential implications for ecosystem health and stability.